pengaruh Motivasi Kerja, Pendidikan Dan Pelatihan (Diklat), Dan Disiplin Kerja Terhadap Kompetensi Pegawai Dan Kinerja Pegawai - Maulana, Rendy Baretta (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
The purpose of this research is to determine the effect of motivation, education and training, and also discipline on the competence and performance of employees. The result of this research indicate that motivation and discipline had no significant effect on competence, but education and training has significant effect on competence. Motivation and competence had significant effect on performance while discipline has no significant effect on performance. Keywords: motivation, training, discipline, competence, performances.